Politik Hukum Antar Bangsa (Siyasah Dauliyah Indonesia Dalam Perdamaian Dunia) - Erfan, Zainul; Hasan, Ahmadi; Umar, Masyitah; Khasyi'in, Nuril (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2024)
Abstract This research explores Indonesia's role in the politics of international law, or Siyasah Dauliyah, in the context of world peace. As one of the important countries in the international arena, Indonesia plays a significant role in maintaining global peace through various initiatives and active participation. Indonesia has long contributed to the mission of world peace, whether through sending peace aid, acting as a negotiator, or becoming a peacemaker in various disputes and conflicts between countries. Indonesia's voice is well heard by other countries, and its strategic role is recognized internationally. Indonesia's Siyasah Dauliyah in world peace not only brings honor to the country's name, but also shows Indonesia's commitment to global stability and security. Indonesia's free, active and democratic foreign policy makes it a country capable of maintaining the global security ecosystem from various turmoil and conflict. Indonesia's participation in international organizations strengthens its role, especially among developing countries on their way to developed country status. In addition to engaging with Non-Aligned countries, Indonesia has also actively forged friendships with developed countries in the Western bloc, strengthening its bargaining power and position in the international arena. Participation in new organizations such as BRICS, which consists mainly of developed countries affiliated with the Eastern bloc, gives Indonesia the benefit of multiple blocs, enhancing its presence and role in international peace, stability and security. Keywords: Politics, Law, Interstate, Peace Abstrak Penelitian ini mengeksplorasi peran Indonesia dalam politik hukum internasional, atau Siyasah Dauliyah, dalam konteks perdamaian dunia. Sebagai salah satu negara penting dalam arena internasional, Indonesia memainkan peran signifikan dalam menjaga perdamaian global melalui berbagai inisiatif dan partisipasi aktif. Indonesia telah lama berkontribusi pada misi perdamaian dunia, baik melalui pengiriman bantuan perdamaian, bertindak sebagai negosiator, maupun menjadi juru damai dalam berbagai sengketa dan konflik antar negara. Suara Indonesia didengar dengan baik oleh negara-negara lain, dan peran strategisnya diakui secara internasional. Siyasah Dauliyah Indonesia dalam perdamaian dunia tidak hanya membawa harum nama negara, tetapi juga memperlihatkan komitmen Indonesia terhadap stabilitas dan keamanan global. Kebijakan luar negeri Indonesia yang bebas, aktif, dan demokratis menjadikannya sebagai negara yang mampu menjaga ekosistem keamanan global dari berbagai gejolak dan konflik. Partisipasi Indonesia dalam organisasi internasional memperkuat perannya, khususnya di antara negara-negara berkembang yang sedang menuju status negara maju. Selain berhubungan dengan negara-negara Non-Blok, Indonesia juga aktif menjalin persahabatan dengan negara-negara maju di blok Barat, memperkuat daya tawar dan posisinya di kancah internasional. Keikutsertaan dalam organisasi baru seperti BRICS, yang sebagian besar beranggotakan negara-negara maju yang terafiliasi dengan blok Timur, memberikan Indonesia manfaat dari berbagai blok, meningkatkan eksistensi dan peranannya dalam perdamaian, stabilitas, dan keamanan dunia internasional. Kata Kunci: Politik, Hukum, Antar negara, Perdamaian